Design of a New Type of Automatic Stair Climbing Wheelchair - Zhu Hua; Wang Zhou; Xia Zaiyan; Zhou Wei; Cai Pengbo (Jixie chuandong)
A new type of automatic stair climbing wheelchair can helps the disabled walking up and down the stairs and the ground is designed.By adopting the leg structure and using the mechanical foot and wheel bearing alternately in the up and down the stairs equipment,the process of up and down the stairs is simulated.The fine-tune mechanism which can be used to adjust seat angle,keep the seats level all the time is set.The change of the gravity center in the process of up and down the stairs is analyzed,the results show that the design of wheelchair is reasonable,a disabled people can use it up and down the stairs instead of walking.